2019
DOI: 10.3386/w25920
|View full text |Cite
|
Sign up to set email alerts
|

What Do Employee Referral Programs Do? Measuring the Direct and Overall Effects of a Management Practice

Abstract: Employee referral programs (ERPs) are randomly introduced in a grocery chain. Larger referral bonuses increase referrals and decrease referral quality, though the increase in referrals from having an ERP is modest. However, the overall effect of having an ERP is substantial, reducing attrition by roughly 15% and decreasing firm labor costs by up to almost 3%. This occurs, partly, because referrals stay longer than nonreferrals, but, mainly, because all workers stay longer in treated than control stores, even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A study by Brown et al (2016) concluded that the employee referral recruitment process could be done quickly; prospective employees already have sufficient information about the company and are likely to be hired for an extended period. Other research conducted by (Friebel et al, 2019) mentioned that the employee referral model would contribute to cost efficiency and avoid conflicts in the workplace.…”
Section: Relationship Between Employees and Business Ownersmentioning
confidence: 99%
“…A study by Brown et al (2016) concluded that the employee referral recruitment process could be done quickly; prospective employees already have sufficient information about the company and are likely to be hired for an extended period. Other research conducted by (Friebel et al, 2019) mentioned that the employee referral model would contribute to cost efficiency and avoid conflicts in the workplace.…”
Section: Relationship Between Employees and Business Ownersmentioning
confidence: 99%
“…First, a number of recent papers have exploited the availability of panel data and more sophisticated identification strategies to estimate the direct effects of referrals, including Bayer et al (2008), Kramarz and Skans (2014), Schmutte (2015), Dustmann et al (2016), Gee et al (2017), andHeath (2018). Alternatively, a number of papers have used experimental settings to generate exogenous variation in the use of referrals; see, e.g., Bandiera et al (2009), Beaman and Magruder (2012), Pallais andSands (2016), andFriebel et al (2019).…”
Section: Related Literaturementioning
confidence: 99%
“…Both papers investigate why referred workers may be more productive than non‐referred workers. In more recent work, Friebel et al (2019) conduct an experiment in a large European grocery chain. By exploiting the variation in the referral programs launched across stores, they assess the value of an employee referral program for the firm.…”
Section: Related Literaturementioning
confidence: 99%